Idiopathic Hypersomnia: Historical Account, Critical Review of Current Tests and Criteria, Diagnostic Evaluation in the Absence of Biological Markers and Robust Electrophysiological Diagnostic Criteria - Billiard, Michel; Sonka, Karel (Nature and science of sleep, 2022)
Idiopathic hypersomnia was first described in 1976 under two forms: polysymptomatic, characterized by excessive daytime sleepiness, long and unrefreshing naps, nocturnal sleep of abnormally long duration and signs of sleep drunkenness upon awakening; monosymptomatic, manifested by excessive daytime sleepiness only. Yet, after 45 years, this sleep disorder is still poorly delineated and diagnostic criteria produced by successive International Classifications of Sleep Disorders are far from satisfactory. The first part of this review is a historical account of the successive names and descriptions of idiopathic hypersomnia: monosymptomatic and polysymptomatic idiopathic hypersomnia in 1976; central nervous system idiopathic hypersomnia in 1979; idiopathic hypersomnia in 1990; idiopathic hypersomnia with and without long sleep time in 2005; idiopathic hypersomnia again in 2014; and, within the last few years, the proposal of separating idiopathic hypersomnia into a well-defined subtype, idiopathic hypersomnia with long sleep duration, and a more heterogeneous subtype combining idiopathic hypersomnia without long sleep duration and narcolepsy type 2. The second part is a critical review of both current ICSD-3 diagnostic criteria and clinical features, scales and questionnaires, electrophysiological and circadian control tests, research techniques, currently used to diagnose idiopathic hypersomnia. The third part proposes a diagnostic evaluation of idiopathic hypersomnia, in the absence of biologic markers and of robust electrophysiological diagnostic criteria.
Keywords: narcolepsy type 1 and narcolepsy type 2; idiopathic hypersomnia; idiopathic hypersomnia without long sleep duration; central disorders of hypersomnolence; idiopathic hypersomnia without long sleep time; idiopathic hypersomnia with long sleep time; narcolepsy; idiopathic hypersomnia with long sleep duration